Digital Evidence in Criminal Procedure: A Comparative Legal Analysis Between Indonesia and The Philippines in Cybercrime Cases - Juhaimen Sumala; Donasto Samosir; Adhalia Septia Saputri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
The acceleration of digital technology development has fundamentally altered the patterns and characteristics of criminal conduct, particularly with the rise of cybercrime that relies predominantly on electronic data as evidence. This shift creates significant challenges within criminal procedural law, especially concerning the admissibility, verification, and credibility of digital evidence in judicial proceedings. This study aims to examine and compare the legal frameworks regulating digital evidence in Indonesia and the Philippines, with an emphasis on procedural aspects in criminal justice systems. The research adopts a normative juridical method utilizing statutory, conceptual, and comparative approaches. The findings reveal that Indonesia’s legal structure, primarily regulated by the ITE Law and the Criminal Procedure Code (KUHAP), remains fragmented and lacks detailed procedural guidelines for handling digital evidence. Conversely, the Philippines demonstrates a more coherent and systematic framework through the Cybercrime Prevention Act of 2012 and the Rules on Electronic Evidence, particularly in ensuring forensic validation and maintaining chain of custody. The originality of this research lies in its comparative focus on procedural differences and its proposal for an integrated legal framework model for Indonesia. The study underscores the urgency of legal reform to enhance evidentiary standards and ensure consistency between substantive and procedural law. Ultimately, strengthening the regulatory framework is essential to guarantee legal certainty and improve the effectiveness of cybercrime law enforcement.